Implementation and use of whole exome sequencing for metastatic solid cancer - Réda, Manon (EBioMedicine, 2020)
BACKGROUND: Genomically-guided clinical trials are performed across different tumor types sharing genetic mutations, but trial organization remains complex. Here we address the feasibility and utility of routine somatic and constitutional exome analysis in metastatic cancer patients. METHODS: Exoma trial (NCT02840604) is a multicenter, prospective clinical trial. Eligible patients presented a metastatic cancer progressing after at least one line of systemic therapy. Constitutional genetics testing required geneticist consultation. Somatic and germline exome analysis was restricted to 317 genes. Variants were classified and molecular tumor board made therapeutic recommendations based on ESMO guidelines. Primary endpoint was the feasibility of the approach evaluated by the proportion of patient that received a therapeutic proposal. FINDINGS: Between May 2016 and October 2018, 506 patients were included. Median time required for tumor sample reception was 8 days. Median time from sample reception to results was 52 days. Somatic analysis was performed for 456 patients (90.1%). Both somatic and constitutional analyses were successfully performed for 386 patients (76.3%). In total, 342 patients (75%) received a therapeutic proposal. Genetic susceptibility to cancer was found in 35 (9%) patients. Only, 79 patients (23.1%) were treated with NGS matched therapy mainly PI3K/AKT/mTOR inhibitors 22 (27.8%), followed by PARP inhibitors 19 (24.1%), antiangiogenics 17 (21.5%), MEK inhibitors 7 (8.9%) and immunotherapy 5 (6.3%). Matched treatment was finally stopped because of disease progression 50 (63%), treatment toxicity 18 (23%), patients’ death 4 (5%). PFS2/PFS1 ratio was > 1,3 for 23,5% of patients treated with the NGS matched therapy and 23,7% of patients treated with standard therapy. INTERPRETATION: Study shows that exome analysis is feasible in cancer routine care. This strategy improves detection of genetic predispositions and enhances access to target therapies. However, no differences were observed between PFS ratios of patients treated with matched therapy versus standard therapy. FUNDING: This work was funding by the centre Georges Francois Leclerc